(untitled) (Journal of Imam Al-Kadhim College, 2023)
Abstract:The exchange of goods has played a very important role in human life, and its form has undergone many changes so that people can meet their needs in easier and safe ways. In the year 2009, the global economy witnessed a new form of transactions that were carried out by digital currencies and it did not face the problems of other transactions. Since then, digital currencies have gradually gained a very important place in global financial and economic relations, This is due to the inability of governments and banks to intervene and the absence of a central bank, in addition to the implementation of all activities such as publishing, processing and validating transactions by the electronic network. One of the most prominent types of digital currencies is the Bitcoin currency, which is used today in many transactions in Islamic and non-Islamic societies and has a huge amount of financial resources. Since this issue is one of the emerging and very important issues whose jurisprudence must be known, this research came to address this subject according to the jurisprudential rulings resulting from knowing the reality of digital currencies “Bitcoin as a model” and their characteristics. And we have concluded that it is permissible to deal in digital currencies by selling and the like; This is due to the problem with the legal evidence mentioned during the research, which was established by the jurists on the prohibition of selling it. Most notably, the sale of these currencies is included in the rule of prohibition of deception.